230k views
1 vote
f(x) = 3x3 + 4x2 – 8x – 2 g(x) = 3x - 5 Find (f - g)(2). A. (f - g)(x) = 3x3 + 4x2 - 11x – 7 B. (f - g)(x) = 3x3 + 4x2 - 11x + 3 C. (f - g)(x) = 3x3 + 4x2 – 5x – 7 D. (f - g)(x) = 3x3 + 4x2 – 5x + 3

f(x) = 3x3 + 4x2 – 8x – 2 g(x) = 3x - 5 Find (f - g)(2). A. (f - g)(x) = 3x3 + 4x-example-1
User Dalinaum
by
5.6k points

1 Answer

5 votes

\begin{gathered} f(x)=3x^3+4x^2-8x-2 \\ g(x)=3x-5 \end{gathered}

Therefore


\begin{gathered} (f-g)(x)=3x^3+4x^2-8x-3x-2-(-5) \\ =3x^3+4x^2-11x+3 \end{gathered}

User Vptheron
by
4.9k points